2014
DOI: 10.3389/fnins.2014.00352
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sex hormone concentrations on decision-making in females and males

Abstract: Human decision-making has been frequently studied and sex differences have been reported. Interestingly, previous results of hormone concentration on decision-making are somewhat inconsistent, regarding the impact of menstrual cycle phase in women or the influence of testosterone concentration on decision-making in women and men. However, the influence of the female sex hormone concentration (estradiol, progesterone) and the impact of oral contraceptive intake have rarely been examined and data regarding the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 60 publications
1
32
0
1
Order By: Relevance
“…Whether this difference of representation could have affected our results is unclear and the literature is contradictory about the effect of gender on the performance at decision-making paradigms [72]. In the standard version of the IGT, some differences have been observed between men and women on the deck choice [73].…”
Section: Discussionmentioning
confidence: 99%
“…Whether this difference of representation could have affected our results is unclear and the literature is contradictory about the effect of gender on the performance at decision-making paradigms [72]. In the standard version of the IGT, some differences have been observed between men and women on the deck choice [73].…”
Section: Discussionmentioning
confidence: 99%
“…Female gonadal hormones, such as estradiol and progesterone (PRO), influence risk-taking behavior (Sukolova and Sarmany-Schuller, 2011; Chavanne and Gallup, 1998; Derntl et al, 2014), and higher levels of estradiol were related to greater impulsivity in the SSRT (Colzato et al, 2010). In animal research, the impact of gonadal hormones on impulsivity has been even less thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…However, these positive associations between testosterone and different indices of risky decision-making have not been unanimously supported. Derntl, Pintzinger, Kryspin-Exner, and Schöpf (2014) failed to find a relationship between testosterone and risky decision-making in both men (n = 45) and women (n = 71), using a battery of laboratory risk-taking measures, including two gambling tasks. Similarly, a study by Zethraeus et al (2009) failed to find a relationship between testosterone and financial risk-aversion, in women.…”
Section: Testosterone Decision-making and Gambling Behaviourmentioning
confidence: 97%
“…However, there are several inconsistencies in this literature. Multiple studies have found null associations between risk-taking and naturally occurring testosterone levels (Derntl et al, 2014;Rosenblitt, Soler, Johnson, & Quadagno, 2001;van der Loos et al, 2013) and high-normal exogenous doses (Boksem et al, 2013;Ortner et al, 2013;Zethraeus et al, 2009). Furthermore, one study has identified clear negative associations between testosterone and several measures of sexual risk-taking attitudes (van Anders, Goldey, Conley, Snipes, & Patel, 2012).…”
Section: Testosterone and Pace Of Playmentioning
confidence: 99%